High-quality Learning: Harder to Achieve Than We Think: A Multicenter Study on Attitudes towards Research among Students - Anshoo Agarwal; S. Anil Mohan Rao (Archives of Current Research International, 2018)
There has been a recorded decrease in the volume of research students who are ready to be Medical researchers in life. Various scientific-based departments have conveyed their worry about career deterioration that lacks the consistent reformation offered by the innovative growth of education. The suggested justification for the decrease in attention to become researcher includes less monetary benefits, responsibilities of family, less career prospects and insufficient introduction to experimental studies before professional routes are decided. Nevertheless, reported survey have registered conflicting viewpoint with regard to its significance with as much as 75% of students preferring to involve in other educational activities as compared to research. In addition, there has been a critical shift towards provision of students with initial practical research within educational program of the school. Considering the requirements and capable attention of designing an undergraduate medical syllabus, as well as the outcomes of viewpoints of other students during medical education, it appears critical to survey the research participation during medical schools as well. The intention of the survey was to examine as for why do pupils wish to be engaged in research, what are the hurdles to effective involvement in research, and if students are sufficiently introduced to methods of research and careers of research. On the scrutiny of information, it was found that 32% of the students only had principal attention in research. 58% had passion in scoring for a "competitive" professional course 61% intended to engage in research so as to facilitate admission to higher professional colleges, 52% of them wanted to involve in research for fame and to get rewards. 57% wished to involve in research because of peer participation .45% implied that research should not be the main criterion for acceptance to higher education .64% mentioned that compulsory research time should be made in syllabus.76% stated that sufficient time was not allotted in the university to pursue research. 69% requires satisfactory training in research methodology in the Universities.